New Strategies and Simulation Tools to Optically Design a Field of Heliostats - Paola Sansoni; Franco Francini; Daniela Fontani; Elisa Sani; Luca Mercatelli; David Jafrancesco (International Journal of Photoenergy)
A heliostats field is an array of mirrors concentrating the solar power on a receiver, typically placed on a tower. Our research experience in the optical design of heliostats fields for Concentrating Solar Power plants suggested using apposite simulation procedures, which were especially developed to simplify the reproduction of heliostats fields and to support in the analysis of the tower plant performances. Our most practically useful simulation tools are presented in this paper with exemplificative application results. The proposed strategies are addressed to solve specific problems and to evidence particularly crucial features. The main program facilitates the heliostats field analysis, exploiting the integration between our software code and Zemax. A side program permits to assess effects of seasonal and daily variations of solar irradiation. Another dedicated side code simplifies the selection of a Compound Parabolic Concentrator as secondary optics.